Kecemasan terhadap Kematian: Peran Perilaku Prososial dan Kebersyukuran pada Lanjut Usia - Afina Zahirah; Herlina Herlina; Anastasia Wulandari (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2020)
This study aims to determine the effect of prosocial behavior on death anxiety moderated by gratitude of the elderly. The research used a quantitative approach. Respondents were 405 elderly aged 60 years and over in Bandung. This study used three instruments: the prosocialness scale, the death anxiety scale (DAS), and the GQ-6. Data were analyzed by linear regression analysis techniques to determine the effect of prosocial on death anxiety, the effect of gratitude on death anxiety, and moderation regression by interacting with the influence of prosocial behavior and gratitude on death anxiety. The results indicate that gratitude increases the effect of prosocial behavior on death anxiety of the elderly in Bandung. The results of this study also found the intensity differences of prosocial behavior, gratitude, and death anxiety of the elderly who live in nursing homes and those who live at home with their families and those who have a history of disease and those who don’t.